Eat it to beat it! ebook Banish belly fat-and take back your health--while eating the brand--name foods you love!. - Zinczenko, David (2013)
NEW YORK TIMES BESTSELLER Eat the World’s Most Delicious Foods—and Start Dropping Pounds Today! Discover thousands of shocking food truths to help flatten your belly fast—and get you on the path to better health!   NBC News health and wellness contributor Dave Zinczenko, author of the multimillion-copy bestselling Eat This, Not That! series, blows the lid off the bizarre, unnecessary, and shocking ingredients in many common brands, and shows you how making smart choices about the foods you love—including burgers, pizza, and chocolate—can help you lose weight, drop blood pressure, boost your immune system, and more.   Discover how you can EAT IT! to help . . .   BEAT IT! WEIGHT GAIN! IHOP’s Chicken and Spinach Salad has as many calories as 6 Klondike Bars! Good news: A similar salad at another restaurant will save you more than 1,200 calories!   BEAT IT! MOODINESS! Some dark chocolate brands contain polyphenols, the near-magical nutrients that improve learning and memory, boost mood, and lower stress levels.   BEAT IT! HIGH BLOOD SUGAR! Can you believe there’s oatmeal on the market with as much sugar per serving as 13 Hershey’s Kisses? Change your breakfast order and start taking control of your blood sugar levels today!   With Eat It to Beat It! , better living starts right now! Praise for Eat It to Beat It!   “David Zinczenko provocatively exposes what’s in our food, so grab a fork and start indulging your way back to health with his advice.” —Mehmet Oz, M.D.   “Dave Zinczenko’s investigations into the truth about our food make him one of the top nutrition experts in America. Eat It to Beat It! is an essential guidebook for anyone with an appetite for eating and living well.” —Travis Stork, M.D., co-host, The Doctors